DAMPAK PENERBITAN SUKUK TERHADAP PROFIL IMAGE BANK UMUM SYARIAH - Savitri, Erni -; Diani, H P; Awaludin, Taufik - (Jurnal Syarikah : Jurnal Ekonomi Islam, 2019)
This study aims to identify whether sukuk issuance can have an impact on increasing the image profile of Islamic banks (IB) among customers and identify dominant aspects assessed by customers regarding religious reputation, financial reputation, bank reputation and management reputation for the issuance of sukuk. The research method used is descriptive analysis, factor analysis and mean analysis. Descriptive analysis is used to explain the demographics of respondents while factor analysis and mean analysis are used to obtain the dominant aspect assessed by the customer for the issuance of sukuk. The results of the study found that respondents concluded that sukuk issuance by Islamic banks could increase the image profile of Islamic banks. As for the dominant aspects assessed by the customer for the issuance of sukuk will increase the religious reputation, bank reputation, financial reputation and reputation of management. The advice given is that other Islamic Banks can consider issuing sukuk, in addition to being useful to increase capital and the amount of financing, IB can also increase the image profile or reputation among customers and investors. A better reputation or image profile can increase the trust of customers and investors to use Islamic banking services. Before issuing sukuk, IB must also consider the condition of financial performance.